Acupuncture for fecal incontinence: Protocol for a systematic review and data mining. Issue 7 (February 2019) - Lin, Haixiong; Zhang, Zhiqing; Hu, Guijuan; Wang, Xiaotong; Lin, Chunni; Chen, Yongjun
Abstract: Background: Fecal incontinence is a socially and emotionally destructive condition that has a negative impact on personal image, self-confidence, and quality of life. Acupuncture is commonly used to treat chronic conditions, including fecal incontinence. However, no relevant systematic review or meta-analysis has been designed to evaluate the effects of acupuncture on fecal incontinence. Methods: We will identify relevant randomized controlled trials (RCTs) from the Cochrane Library, Medline, Embase, PubMed, Springer, Web of Science, China National Knowledge Infrastructure, VIP Chinese Science and Technology Journals Database, Wanfang database, and clinical trial registration center from their inception to February 28, 2019. The primary outcome measures will be clinical effective rate, functional outcomes, and quality of life. Data that meets the inclusion criteria will be extracted and analyzed using RevMan V.5.3 software. Two reviewers will evaluate the studies using the Cochrane Collaboration risk of bias tool. Publication bias will be assessed by funnel plots, Egger test, and Begg test using the Stata software. Acupoints characteristics will be analyzed by Traditional Chinese Medicine inheritance support system. Results: This study will analyze the clinical effective rate, functional outcomes, quality of life, daily average number of fecal incontinence, and effective prescriptions of acupuncture for patients with fecal incontinence. Conclusion: Our findings will provide evidence for the effectiveness and potential treatment prescriptions of acupuncture for patients with fecal incontinence. PROSPERO registration number: PROSPERO CRD42019119680.